2008
DOI: 10.1093/cercor/bhm261
|View full text |Cite
|
Sign up to set email alerts
|

Brain Size and Folding of the Human Cerebral Cortex

Abstract: During evolution, the mammalian cerebral cortex has expanded disproportionately to brain volume. As a consequence, most mammals with large brains have profusely convoluted cortices. The human cortex is a good example of this trend, however, given the large variability in human brain size, it is not clear how cortical folding varies from the smallest to the largest brains. We analyzed cortical folding in a large cohort of human subjects exhibiting a 1.7-fold variation in brain volume. We show that the same disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
201
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(215 citation statements)
references
References 35 publications
14
201
0
Order By: Relevance
“…It shows that handling ICV differences in folding studies may not be as simple as including ICV as a covariate in the underlying statistical test. This paper proposes two systematic methods for handling ICV changes in folding studies using the proposed descriptor and shows that while the findings using one method are consistent with [10], those using the other method are consistent with [11,12].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…It shows that handling ICV differences in folding studies may not be as simple as including ICV as a covariate in the underlying statistical test. This paper proposes two systematic methods for handling ICV changes in folding studies using the proposed descriptor and shows that while the findings using one method are consistent with [10], those using the other method are consistent with [11,12].…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, while one study [10] using the fractal-dimension (FD) measure reported higher complexity in adult females, two very recent studies [11,12] using the isoperimetric ratio (IPR) measure report higher complexity in larger adult brains (i.e. males).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a data set of human subjects (Pausova et al, 2007) was analyzed by Toro et al (2008). These data (314 subjects, 164 females and 150 males of 12-20 years old) are presented in Figure 1c.…”
mentioning
confidence: 99%
“…Judging from the human data ( Fig. 1d) and taking 290 the data of (Toro et al, 2008) as a reference, it seems that systematic errors may be considerable, depending on the author. The sphericity parameter, s had a standard deviation (SD) of 0.09.…”
mentioning
confidence: 99%